Corticobasal syndrome as a focal variant of Alzheimer’s disease (2022)
We present a 60-year-old woman with a 2-year history of progressive anterograde memory deficit, that evolved with a typical corticobasal syndrome with extrapyramidal signs and left superior limb dystonia. 18F-FDG and 11C-PIB PET/CT studies supported the diagnosis of Alzheimer’s disease associating a corticobasal syndrome.